Can a mobile credit-scoring model provide better accessibility to South African citizens requiring micro-lending?. (9th April 2019) - Hendricks, Matthew Kenneth; Budree, Adheesh
This paper investigates developing a conceptual model for credit scoring microfinance in South Africa. This poses an issue as the demand for micro-lending arise primarily from the lowest income groups who are normally found in rural or peri-urban areas and are not easily accessible. Current literature and research on credit scoring models within microfinance for low-income groups was found to be extremely limited. Based on current research, this paper assessed the use of collateral and collateral substitutes, innovative methods behind credit scoring and mobile technology which could drive a credit scoring model to provide access to underprivileged citizens. Based on the findings of this study, a best practice conceptual model that develops a form of credit scorecard based on an applicant's social media credit score, psychometric score, mobile credit score and the presence of collateral and collateral substitutes that can help increase accessibility of microfinance to underprivileged recipients was developed.